Progress in development of 'asexual' maize - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A high-yielding maize variety that farmers can plant year after year without having to buy new seed sounds like an impossibledream. But scientists at the Centre for the Improvement of Wheat and Maize (CIMMYT) in Mexico have taken the first...